Effectiveness and Safety of Niraparib as Neoadjuvant Therapy in Advanced Ovarian Cancer With Homologous Recombination Deficiency (NANT): Study Protocol for a Prospective, Multicenter, Exploratory, Phase 2, Single-Arm Study - Zhou, Dongchen; Liu, Jiahao; Liu, Ronghua; Li, Huayi; Huang, Yi; Ma, Ding; Hong, Li; Gao, Qinglei (Frontiers in Oncology, 2022)
Background Ovarian cancer (OC) is a heterogeneous gynecological malignancy with a poor prognosis as the majority of patients are diagnosed at an advanced stage. Neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS) is recommended for patients who cannot achieve optimal cytoreduction or cannot endure primary debulking surgery (PDS). As there is an increased risk of chemoresistance for platinum-based NACT, it is important to investigate an alternative option. A Poly (ADP-ribose) polymerase inhibitor (PARPi), niraparib, has shown high anti-tumor activity, especially in homologous recombination deficiency (HRD) positive patients with OC. Thus, niraparib as a neoadjuvant treatment agent may help improve surgery accessibility and create survival benefits. Methods This multicenter, prospective, single-arm, open-label, phase II study plans to recruit 53 patients (aged 18-75 years) with newly diagnosed HRD positive, unresectable (Fagotti score ≥ 8 or upper abdominal computed tomography [CT] score ≥ 3) International Federation of Gynecology and Obstetrics (FIGO) stage III-IV OC. The HRD status was detected by next-generation sequencing and HRD positive patients will be counseled for study participation. Enrolled patients will receive niraparib capsules QD (200mg or 300mg per day) for two cycles (4 weeks/cycle). After neoadjuvant niraparib treatment, patients exhibiting complete response (CR), partial response (PR), or stable disease (SD) will undergo tumor reduction surgery and subsequent standard carboplatin/paclitaxel-based chemotherapy. The primary objectives include the objective response rate (ORR) and R0 resection rate. The rate of treatment interruption/termination and progression-free survival (PFS) will be secondary objectives. The study uses Simon’s optimal two-stage design (24 and 21 patients for the first and second stage respectively). The data manager will record all adverse events (AEs). Discussion This is the first prospective study to evaluate the effectiveness and safety of niraparib in neoadjuvant treatment for advanced OC. The result of this study will provide a solid base for further expanding the clinical applications of the PAPRi and exploring more therapeutic possibilities for patients with HRD positive advanced OC. Clinical Trial Registration: https://clinicaltrials.gov/, identifier NCT04507841.